Características del paro cardiaco extrahospitalario atendido por operadores de ambulancias en Medellín. Estudio de cohorte retrospectivo de base poblacional (2024)
ABSTRACT: Introduction: Every year, five million people around the world experience an out-of-hospital cardiac arrest (OHCA) and less than 40 % receive any assistance before the arrival of the Emergency Medical Services (EMS). Ambulance operators (AO) take care of people experiencing an OHCA, stabilize and then transfer them. In Medellín, Colombia, there is a public AO and several private providers, but the information about an OHCA and the operational characteristics during the response to the event are limited. Objective: To estimate the incidence of OHCA and to explore the factors associated with survival after the event in Medellín city. Methods: Retrospective, population-based cohort study. All the medical records of patients experiencing an OHCA who were assessed and treated by ambulance operators, (AO) of the Emergency Medical Services (EMS) and private agencies in Medellin city were reviewed. Descriptive statistics were used for data analysis and the annual incidence of the event standardized for the general population was estimated. Potential survival-associated factors reported as OR with their corresponding 95% CI were explored. Results: A total of 1,447 patient records with OHCA between 2018 and 2019 were analyzed. The event incidence rate for the number of cases assessed was 28.1 (95 % CI 26.0-30.3) and 26.9 (95 % CI 24.9-29.1) cases per 100,000 inhabitants/year for 2018 and 2019, respectively; the incidence rate of treated OHCA was 2.6 (95 % CI 2.0-3.3) and 3.2 (95 % CI 2.5-4.0) per 100,000 inhabitants/year, for 2018 and 2019. Survival on arrival at hospitals of treated cases was 14.2 % (95 % CI 5.5-22.8) and 15.5 % (95 % CI 7.4-23.5) for 2018 and 2019, respectively. Conclusions: This study portrays the operating and care characteristics of the population experiencing OHCA in Medellín city. The incidence rate of the event and the survival were lower than those reported in the literature.